A conceptual framework for cooperative risk management in seaports. (16th October 2022) - Nagi, Ayman; Schroeder, Meike; Kersten, Wolfgang
This study aims to develop a conceptual framework to guide the future research and development of a prescriptive process model for cooperative risk management in seaports (CoRiMaS). An empirical interview study based on 15 semi-structured interviews carried out in the Port of Hamburg served as input for the framework development. The empirical study is also supported by theories extracted from risk management, process management, knowledge management, and network science. The conceptual framework provides an overview of the required aspects to facilitate efficient cooperation in risk management, such as the definition of clear steps and guidelines for the proactive and reactive risk management process. According to the authors' knowledge, this study presents the first conceptual framework that provides sufficient practical means to facilitate CoRiMaS and guide future research in this field.